Designing a Framework for Evaluating the Scientific Productions - Ali Norouzi; Parastoo Parsaei- Mohammadi; Ehsan Geraei; Firoozeh Zare-Farashbandi (International Journal of Preventive Medicine)
Background: Evaluation of scientific productions to attract, maintain, and promote faculty members is one of the necessary processes of academic societies and is of interest to policy makers in the field of higher education. This study aimed to provide a uniform and native framework for evaluating the scientific productions of researchers in the fields of science and health in Iran. Methods: The current research used the single-stage fuzzy Delphi technique and AHP. The research community comprised 50 top scientific experts and researchers from the country. The data collection tool was a researcher-made checklist obtained from the review of literature and laws and regulations of Iranian universities and research institutions. Results: Data analysis led to the identification, prioritization and weighting of eleven criteria and 124 items for the intended framework, which are, respectively, author’s authority (scientific leaders) (15 items); database used in calculating the index (3 items); Innovation and technological impact (18 items); Gaining rank in national and international festivals related to the specialized field (6 items); Citations (7 items); subject area (3 items); level of cooperation (15 items); Types of scientific productions (54 items); scientific age (3 items); Evaluating, refereeing and monitoring of research, technology and innovation activities (2 items) Author`s role and position (1 item). Conclusion: The final framework obtained for evaluating Iranian researchers has 11 criteria and 124 items that can be used to compile an author-centered and native scientometrics index that leads to the same evaluation of health and science researchers.